2016
DOI: 10.1093/ndt/gfw333
|View full text |Cite
|
Sign up to set email alerts
|

Snail and kidney fibrosis

Abstract: Snail family zinc finger 1 (SNAI1) is a transcription factor expressed during renal embryogenesis, and re-expressed in various settings of acute kidney injury (AKI). Subjected to tight regulation, SNAI1 controls major biological processes responsible for renal fibrogenesis, including mesenchymal reprogramming of tubular epithelial cells, shutdown of fatty acid metabolism, cell cycle arrest and inflammation of the microenvironment surrounding tubular epithelial cells. The present review describes in detail the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 100 publications
2
32
0
Order By: Relevance
“…As shown in Figure e–g, the protein expression levels of the active and total form of β‐catenin were significantly upregulated following the development of aging. We then inspected PAI‐1, Snail1, and MMP‐7, the three important targets that reflect the activity of Wnt/β‐catenin signaling (He et al, , ; Simon‐Tillaux & Hertig, ). As shown in Figure e,h,i, the expression levels of PAI‐1 and Snail1 were significantly induced in aging mice, especially in 24‐month‐old mice.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure e–g, the protein expression levels of the active and total form of β‐catenin were significantly upregulated following the development of aging. We then inspected PAI‐1, Snail1, and MMP‐7, the three important targets that reflect the activity of Wnt/β‐catenin signaling (He et al, , ; Simon‐Tillaux & Hertig, ). As shown in Figure e,h,i, the expression levels of PAI‐1 and Snail1 were significantly induced in aging mice, especially in 24‐month‐old mice.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined potential inflammatory signals expressed by the collecting duct on the basis of existing evidence. 40 We looked at the differential expression of KLF5, P2ry14, and Snail 40,41,55,56 and found no significant difference between SKO and DKO kidneys (Supplemental Figure 10, A-C). It is likely that signals other than the ones evaluated above underlie the chronic kidney injury phenotype observed in the DKO mice.…”
Section: Ckd Occurs Due To Loss Of Xbp1s Homeostatic Activity In the mentioning
confidence: 99%
“…The expression of Snail correlated with tumor grade, metastasis and could be used as a prognostic marker for poor outcome in patients with head and neck squamous cell carcinoma . In addition, several studies have shown that Snail was related to various fibrosis . As such, targeting Snail may be a promising therapeutic approach to attenuate the progression of precancerous OSF.…”
Section: Introductionmentioning
confidence: 99%